Developing communicative competence in philology students through artificial intelligence tools - Nasirova, Umida Kamolovna (The Lingua Spectrum, 2026)
This paper explores the systematic development of communicative competence in philology students through the strategic integration of artificial intelligence (AI) technologies in higher education. The study is firmly grounded in a competency-based approach, emphasizing the formation of linguistic, sociolinguistic, discourse, and strategic components essential for modern philologists. Artificial intelligence tools are examined not merely as supplementary aids, but as transformative pedagogical instruments that facilitate interactive learning, individualized instruction, and authentic language practice. The paper provides an in-depth discussion of the linguodidactic principles underlying the implementation of AI-driven platforms in English language teaching, highlighting their potential to foster both academic and professional communication skills. By analyzing specific platforms and digital tools, the findings suggest that the integration of AI contributes to a more dynamic, adaptive, and student-centered educational environment. Ultimately, this approach supports the comprehensive development of communicative competence, preparing students for the complexities of global professional discourse in the digital age.